Comparative Analysis Of Applications OSforensics, GetDataBack, Genius and Diskdigger On Digital Data Recovery in the Computer Device - Hidayat, Arif; ., Sudarmaji; ., Dharmawan; Irawan, Dedi; Joko Susanto, Lilik; ., Mustika; Pranoto, Hadi (International Journal of Engineering and Technology, 2018)
In the use of computer devices that are done in recent use for data processing in the form of text, images or video that can be done easily and quickly. But in reality, there are events where the work, in the form of computer files, can be lost so that the required files are missing from the storage media in the computer. In this research will be discussed and presented a comparative analysis of four software for recovery of data that has been deleted. The applications used are OSforensics, GetDataBack, Disk Genius and Diskdigger. The capabilities of such applications in the recovery of deleted data have been tested and analyzed in flash drives. Based on the tests that have been done indicates that the fourth this application can work well in terms of finding deleted data. In addition, this application is also able to recover data or retrieve the already deleted.Â